Defence in a Changing World: How Defensive Should (NATO) Defence Be? - Voss, Mathias (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
The author takes the reader on a swift and sweeping ride through different aspects of defence. What is the core of defence in general? And what is defence today for the most prominent of all defensive alliances, for NATO, which is in the midst of a reflection process on what its role in the future should be?The notoriously vague and shadowy term “defence” is illuminated from different angles, culminating in the newly introduced model of “strategical analysis”. The historical perspective comprises examples varying from China’s Great Wall to the Israeli-Arab Six Days War and NATO’s history with a specific focus on its understanding of defence from its foundation, through all three ages of its existence and into today’s still and again changing world. More insights are drawn from the application of the prevalent judicial, political and military strategic approaches and terms.From this kaleidoscopic view, the author draws practical conclusions and formulates clear and pointed recommendations for the persistent and particularly in NATO very current discussion about how the understanding of defence should – or should not – evolve.